Intelligent collaborative management technology of virtual resources based on internet of vehicles remote driving - Xinyu PENG; Yang ZHOU; Zhenjiang DONG (Dianxin kexue)
Starting from the application scenario of internet of vehicles remote driving,the specific requirements of remote driving for network communication were analyzed.The technical analysis scheme was put forward systematically.First of all,mobile edge computing technology was introduced on the terminal side to provide,low latency,large bandwidth and high reliability edge computing services.Secondly,virtual resource cooperative scheduling and intelligent fault prediction technology were analyzed on the network side,to complete the global management of network resources for remote driving.Finally,the related technologies of the intelligent vehicle integrated control service and SDN cloud control center were analyzed on the platform side,so that the intelligent application of remote driving vehicle was realized.